Methods for evaluating the physiological potential of scarlet eggplant (Solanum aethiopicum) seeds - Lopes, M. M. [UNESP]; Barbosa, R. M. [UNESP]; Vieira, R. D. [UNESP] (My University, 2012)
The use and efficiency of vigour tests depend on the plant species and the development and / or adjustment of methodology to obtain efficient procedures for evaluating seed physiological potential. The objective of this study was to compare different methods for evaluating the physiological potential of scarlet eggplant seeds (Solanum aethiopicum Scarlet eggplant Group). Six seed lots of the Morro Grande' cultivar were submitted to the following tests: germination, first count germination, seedling emergence, controlled deterioration (18, 21 and 24% for 24 and 48 hours at 45°C), accelerated ageing (AA) and saturated salt accelerated ageing (SSAA; NaCl) both at 41 and 45°C for 24, 48 and 72 hours) and electrical conductivity (25 and 50 seeds; 25, 50 and 75 mL of deionised water for 1, 2, 4, 8, 12, 16 and 24 hours of imbibition at 25°C). With the exception of electrical conductivity, results from the first count test and for specific times / temperatures of the other tests, generally showed similar ranking of the lots as seen for seedling emergence. It was concluded that the physiological potential of scarlet eggplant seeds can be evaluated using AA and SSAA for 48 h / 41°C and controlled deterioration at 24% moisture content / 24 h / 45°C, thus classifying the seed lots into different vigour levels.